2003
DOI: 10.1083/jcb.200209019
|View full text |Cite
|
Sign up to set email alerts
|

Contact inhibition of VEGF-induced proliferation requires vascular endothelial cadherin, β-catenin, and the phosphatase DEP-1/CD148

Abstract: Confluent endothelial cells respond poorly to the proliferative signals of VEGF. Comparing isogenic endothelial cells differing for vascular endothelial cadherin (VE-cadherin) expression only, we found that the presence of this protein attenuates VEGF-induced VEGF receptor (VEGFR) 2 phosphorylation in tyrosine, p44/p42 MAP kinase phosphorylation, and cell proliferation. VE-cadherin truncated in β-catenin but not p120 binding domain is unable to associate with VEGFR-2 and to induce its inactivation. β-Catenin–n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
389
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(415 citation statements)
references
References 60 publications
24
389
1
1
Order By: Relevance
“…However, no difference in paracellular PECAM-1 immunoreactivity was observed. These in vivo observations reflect those of in vitro studies where declustering of VE-cadherin and β-catenin, as shown by loss of junctional immunostaining and immunoblotting, resulted in increased proliferation and decreased barrier function [14,15,22]. Transfection of a recombinant VE-cadherin (cytoplasmic domain only) into intact isolated coronary venules has also been seen to result in markedly higher albumin permeability; competition between the recombinant VE-cadherin and the endogenous VEcadherin blocked the association with β-catenin and the maintenance of junctional integrity and microvascular permeability [30].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, no difference in paracellular PECAM-1 immunoreactivity was observed. These in vivo observations reflect those of in vitro studies where declustering of VE-cadherin and β-catenin, as shown by loss of junctional immunostaining and immunoblotting, resulted in increased proliferation and decreased barrier function [14,15,22]. Transfection of a recombinant VE-cadherin (cytoplasmic domain only) into intact isolated coronary venules has also been seen to result in markedly higher albumin permeability; competition between the recombinant VE-cadherin and the endogenous VEcadherin blocked the association with β-catenin and the maintenance of junctional integrity and microvascular permeability [30].…”
Section: Discussionsupporting
confidence: 73%
“…This strengthens the hypothesis that increased VEGF levels are part of the mechanism resulting in the junctional perturbations observed in Type 1 diabetic placentae. Although the signalling properties of VE-cadherin and β-catenin are largely VEGF induced [9,22], the levels of other angiogenic growth factors, such as placental growth factor, basic fibroblast growth factor and angiopoetins 1 and 2, may influence vascular development and maturity in the diabetic placenta and should be monitored [9,38]. Differences in the immunostaining intensity of placental VEGF receptor-1 (but not receptor-2) have been reported in cases of Type 1 diabetes [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported that cadherins interact with growth factor receptors, including VE-cadherin with vascular endothelial growth factor (VEGF) receptor, N-cadherin with FGF receptor, and E-cadherin with EGFR (Williams et al, 2001;Lampugnani et al, 2003;Qian et al, 2004). Cadherins have been found to influence growth factor receptor signaling, either activating (Pece and Gutkind, 2000) or inhibiting (Takahashi and Suzuki, 1996;Qian et al, 2004) signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Third, VEGF induces VE-cadherin association with the adaptor molecule Shc, and this Lampugnani et al 2003 association increases Shc dephosphorylation, probably through the action of junctional phosphatases ( ). As Shc is Zanetti et al 2002 known to activate the MAP kinase pathway, its capture at the junction by VE-cadherin and its subsequent dephosphorylation may interfere with the VEGF proliferative signal.…”
Section: Cell Cycle Arrestmentioning
confidence: 99%